2023
DOI: 10.3390/jcm12227132
|View full text |Cite
|
Sign up to set email alerts
|

Drug Clearance in Patients with Inflammatory Bowel Disease Treated with Biologics

Tina Deyhim,
Adam S. Cheifetz,
Konstantinos Papamichael

Abstract: Biological therapy is very effective for treating patients with moderate to severe inflammatory bowel disease (IBD). However, up to 40% can have primary non-response, and up to 50% of the patients can experience a loss of response to anti-tumor necrosis factor therapy. These undesirable outcomes can be attributed to either a mechanistic failure or pharmacokinetic (PK) issues characterized by an inadequate drug exposure and a high drug clearance. There are several factors associated with accelerated clearance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
(131 reference statements)
0
1
0
Order By: Relevance
“…Pharmacokinetic studies have demonstrated that obese patients have increased drug clearance of anti-TNF with shortened half-life and lower trough drug concentrations compared with normal-weight patients (15)(16)(17). In addition, it has been found that patients with higher visceral adiposity required higher IFX troughs (13.6-15.9) as compared with patients with lower visceral adiposity (3.9-4.9) to maintain steroid-free and endoscopic remission (18).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic studies have demonstrated that obese patients have increased drug clearance of anti-TNF with shortened half-life and lower trough drug concentrations compared with normal-weight patients (15)(16)(17). In addition, it has been found that patients with higher visceral adiposity required higher IFX troughs (13.6-15.9) as compared with patients with lower visceral adiposity (3.9-4.9) to maintain steroid-free and endoscopic remission (18).…”
Section: Discussionmentioning
confidence: 99%
“…However, since many cancer drugs are hydrophobic, injecting the appropriate drug concentration required for treatment is difficult, and direct drug injection often causes side effects owing to non-specific effects on cancer and normal cells [16][17][18][19]. Additionally, the injected drugs are removed by the reticuloendothelial system (RES), and only a small fraction of the drug is delivered to the cancer cells, making it difficult to reach a sufficient concentration for treatment [20][21][22][23][24]. Drug delivery systems have been developed over the past few years [25][26][27].…”
Section: Introductionmentioning
confidence: 99%